Pemindai intraoral 3d pada Ortodonti: tinjauan naratif - Andira Lusiana; Fajar Hamonangan Nasution (Fakultas Kedokteran Gigi Universitas Trisakti, 2023)
Background: Nowadays, 3D intraoral scanners have become an ongoing trend in the development of digital orthodontics. Its utility is to minimize patient discomfort during scanning while maximizing the accuracy of the images and shortening the diagnosis time. Objective: To determine the accuracy of 3D intraoral scanners in orthodontics in cases of crowded teeth. Methods: The study was conducted by narrative review by PRISMA guidelines and using electronic databases, PubMed, Google Scholar, and ScienceDirect which were then processed and reviewed. Results: Four journals were found, which were then presented in the extraction table. Each journal discusses the accuracy of 3D intraoral scanners in orthodontics in cases of crowded teeth using their respective research methods. Conclusion: The 3D intraoral scanner showed no significant difference in the accuracy of the study models in the case of crowded teeth. Clinically, the 3D intraoral scanner is acceptable for diagnosis and treatment planning in dentistry.